2023
DOI: 10.3389/fmicb.2023.1133968
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic impact of nanomaterials and plant probiotics in agriculture: A tale of two-way strategy for long-term sustainability

Abstract: Modern agriculture is primarily focused on the massive production of cereals and other food-based crops in a sustainable manner in order to fulfill the food demands of an ever-increasing global population. However, intensive agricultural practices, rampant use of agrochemicals, and other environmental factors result in soil fertility degradation, environmental pollution, disruption of soil biodiversity, pest resistance, and a decline in crop yields. Thus, experts are shifting their focus to other eco-friendly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 257 publications
0
7
0
Order By: Relevance
“…Research studies on various intra- and extracellular enzymes have also been used to evaluate the potential benefits of applying NPs and PGPR simultaneously. Soil urease and dehydrogenase enzymes activity was enhanced by applying PGPR and NPs compared to single-use of any of them ( Alharbi et al., 2023 ; Upadhayay et al., 2023 ). Jabborova et al.…”
Section: Catalyzing Soil Enzyme Activity With Nanoparticles and Pgprmentioning
confidence: 99%
See 2 more Smart Citations
“…Research studies on various intra- and extracellular enzymes have also been used to evaluate the potential benefits of applying NPs and PGPR simultaneously. Soil urease and dehydrogenase enzymes activity was enhanced by applying PGPR and NPs compared to single-use of any of them ( Alharbi et al., 2023 ; Upadhayay et al., 2023 ). Jabborova et al.…”
Section: Catalyzing Soil Enzyme Activity With Nanoparticles and Pgprmentioning
confidence: 99%
“…Adding specific substances to the soil enhances its capacity to sustain plant life ( Urra et al., 2019 ; Rubin et al., 2023 ; Kumari et al., 2023b ). Plant growth-promoting rhizobacteria (PGPR) and nanomaterials (NMs) or nanoparticles (NPs) are under consideration as a novel approach to boost crop productivity and soil fertility ( El-Ramady et al., 2022 ; Upadhayay et al., 2023 ; Rajput et al., 2023a ; Kumari et al., 2024 ). Several research studies have demonstrated numerous benefits that soil organic amendments may provide, including better soil texture, higher soil fertility, restored soil health, and, ultimately, higher crop yield ( Urra et al., 2019 ; Rani et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials and nanoparticles (NPs) have attracted the global attention for their widespread application in almost all sectors including modern agricultural practices ( Zain et al., 2022 ; Chauhan and Gill, 2023 ). Nano-agrochemicals have vast potential in complementing the growth, development and yield of crop plants along with resilience to variety of biotic and abiotic stress factors ( Liliane and Charles, 2020 ; Shahzad et al., 2021 ; Beig et al., 2022 ; Upadhayay et al., 2023 ). Among NPs, titanium dioxide nanoparticles (TiO 2 NPs) are reported to be widely used NPs in paints, sunscreen, paper, antibacterial fiber, fine ceramics, plastic, food additives due to their anti-UV, antibacterial, self-cleaning, anti-aging, anti-fading, chemical inertness, photocatalytic activity ( Hendren et al., 2011 ; Kovačič et al., 2022 ).…”
Section: Effect Of Nano-titanium Dioxide On Mulberry: Transcriptomics...mentioning
confidence: 99%
“…Plant growth-promoting microorganisms, also identified as "Plant Probiotics (PPs)", have gained recognition. As bio-elicitors, PPs promote plant growth and colonize soil or plant tissues when administered in soil, seeds, or plant surface and are used as an alternative means to avoid heavy use of agrochemicals (Upadhayay et al 2023 ). In addition, agrochemicals have shown a significant increase in crop yields in the past few decades, but adverse effects have emerged later from overuse of chemical fertilizers.…”
Section: Introductionmentioning
confidence: 99%